A new computational strategy for optimal control problem with a cost on changing control - Wang, Y.; Yu, C.; Teo, Kok Lay (American Institute of Mathematical Sciences, 2016)
© 2016 American Institute of Mathematical Sciences. All rights reserved.In this paper, we consider a class of optimal control problems where the cost function is the sum of the terminal cost, the integral cost and the full variation of control. Here, the full variation of a control is defined as the sum of the total variations of its components. By using the control parameterization technique in conjunction with the time scaling transformation, we develop a new computational algorithm for solving this type of optimal control problem. Rigorous convergence analysis is provided for the new method. For illustration, we solve two numerical examples to show the effectiveness of the proposed method.